Mathematics in Engineering Education: a Review of the Recent Literature with a View towards Innovative Practices - Pepin, Birgit; Biehler, Rolf; Gueudet, Ghislaine (International Journal of Research in Undergraduate Mathematics Education)
Abstract The aim of the special issue is to bring together important current international research on innovative teaching and learning practices in mathematics in engineering education, and to develop deeper understandings of the characteristics of current teaching and learning practices that can inform the design and implementation of future innovative practice. The focus of this review paper is to provide a state-of-the-art overview of this emerging field at the cross-roads between mathematics and engineering education, in addition to introducing the papers of this special issue. To guide this paper, we posed three review questions: (1) How can current (teaching/learning/study) practices of mathematics in engineering education be characterized with a view towards innovation?; (2) What are the ‘resources’ (cognitive, material, digital, social) used, and what are those that appear also well suited for innovative courses?; (3) What are promising innovative practices in mathematics in engineering education, and what are the implications for curriculum reform? Looking back across the studies we summarized in the review, we conclude that they are lagging behind the more fundamental changes that are happening in engineering education, whilst addressing selected aspects of innovative changes within the current system of engineering education. At the same time, the nine papers of this special issue contribute new perspectives for innovative practices in mathematics in engineering education, for a better understanding of current practices and for future research.
Keywords: Education; Mathematics (miscellaneous)

Design-Based Research in der Hochschullehre am Beispiel der Lehrveranstaltung „Einführung in die Kultur der Mathematik“ - Kempen, Leander; Biehler, Rolf (Lehrinnovationen in der Hochschulmathematik . Konzepte und Studien zur Hochschuldidaktik und Lehrerbildung Mathematik)

Education and professional development of university mathematics teachers - Winsløw, Carl; Biehler, Rolf; Jaworski, Barbara; Rønning, Frode; Wawro, Megan (Research and Development in University Mathematics Education)

Schatten von 3D-Objekten: Modellierung mit GeoGebra 3D und Anwendungen in der Computergrafik - Höper, Lukas; Malin, Leah; Biehler, Rolf (mathematik lehren)

Faszination 3D-Film: Entwicklung einer 3D-Konstruktion - Hüsing, Sven; Weiser, Niklas; Biehler, Rolf (mathematik lehren)

Consultation Phases in Mathematics Learning and Support Centres - Schürmann, Mirko; Panse, Anja; Shaikh, Zain; Biehler, Rolf; Schaper, Niclas; Liebendörfer, Michael; Hilgert, Joachim (International Journal of Research in Undergraduate Mathematics Education)
Abstract Mathematics Learning Support Centres are becoming more and more common in higher education both internationally and in Germany. Whereas it is clear that their quality largely depends on a functioning interaction in consultations, little is known about how such consultations proceed in detail. On the basis of models from the literature and recorded support sessions (N = 36), we constructed a process model that divides consultations into four ideal–typical phases. In the individual consultations, forward or backward leaps occur, but overall the model seems to describe the data well. A high intercoder reliability shows that it can be applied consistently on real data by different researchers. An analysis of the consultations between students and tutors shows that both mainly work on past attempts or thoughts of the students to solve the exercise or problems and on concrete strategies to solve a problem within the session. In contrast, very little time is dedicated to summarizing and reflecting the solution. The data allows for a more in-depth discussion of what constitutes quality in advising processes and how it might be further explored. Practically, the model may structure support sessions and help in focussing on different goals in different phases.
Keywords: Education; Mathematics (miscellaneous)

The process of actively building a model for a randomization test – insights into learners’ modeling activities based on a case study - Podworny, Susanne; Biehler, Rolf (Mathematical Thinking and Learning)
Keywords: Developmental and Educational Psychology; Education; General Mathematics

A first introduction to data science education in secondary schools: Teaching and learning about data exploration withCODAPusing survey data - Frischemeier, Daniel; Biehler, Rolf; Podworny, Susanne; Budde, Lea (Teaching Statistics)
Keywords: Education; Statistics and Probability

Transforming into a Platform Provider: Strategic Options for Industrial Smart Service Providers - Beverungen, Daniel; Kundisch, Dennis; Wünderlich, Nancy (Journal of Service Management)
Purpose The purpose of this paper is to identify strategic options and challenges that arise when an industrial firm moves from providing smart service toward providing a platform. Design/methodology/approach This conceptual study takes on a multidisciplinary research perspective that integrates concepts, theories and insights from service management and marketing, information systems and platform economics. Findings The paper outlines three platform types – smart data platform, smart product platform and matching platform – as strategic options for firms that wish to evolve from smart service providers to platform providers. Research limitations/implications Investigating smart service platforms calls for launching interdisciplinary research initiatives. Promising research avenues are outlined to span boundaries that separate different research disciplines today. Practical implications Managing a successful transition from providing smart service toward providing a platform requires making significant investments in IT, platform-related capabilities and skills, as well as implement new approaches toward relationship management and brand-building. Originality/value The findings described in this paper are valuable to researchers in multiple disciplines seeking to develop and to justify theory related to platforms in industrial scenarios.
Keywords: Smart service; Platform; Interdisciplinary research; Manufacturing company; Smart service provider; Platform economics; Information systems; Multi-sided markets; Business-to-business (B2B) markets

Tax Burden on German Companies – Income Tax Burden and Administrative Costs - Fochmann, Martin; Heile, Vanessa; Huber, Hans-Peter; Maiterth, Ralf; Sureth-Sloane, Caren

Musik als Lebensmittel. Kulturwissenschaftlich-theologische Rationen für ein Jahr

Die Studieneingangsphase. Einführung in die hochschuldidaktische Herausforderung und Entwicklung eines Kriterienrasters unter Bedingungen der Digitalisierung - Reis, Oliver (Habitusbildung in der Studieneingangsphase. Reflexionen zu einem hybriden Modell)

Transformationen des hochschuldidaktischen Dreiecks im Kontext der Digitalisierung - Reis, Oliver (Theologiestudium im digitalen Zeitalter)

Digitalisierung als Motor einer neuen (totalen) Form der instruktionsorientierten Lernsteuerung? - Reis, Oliver (Habitusbildung in der Studieneingangsphase. Reflexionen zu einem hybriden Modell)

Kraml, Martina: Anderes ist möglich. Eine theologiedidaktische Studie zu Kontingenz im Raum der Wissenschaften (Kommunikative Theologie 19). Matthias Grünewald Verlag, Ostfildern 2018. (490) - Reis, Oliver (ThPQ)

Wenn Gremien in die Jahre kommen…Wie baut man die Gremienstruktur in den Pastoralen Räumen um, damit sich Gemeinden zukunftsfähig entwickeln können? - Burke, Rebekka; Hackstedt, Carola; Hofmeister, Lisa; Kolk, Matthias; Rakowski, Jana; Reis, Oliver (Projektbericht 1: Modelle, Transformationen, Corona-Erfahrungen)

Steuerung vs. Kontingenz: die Umsetzung gesetzter und realer Strukturinterventionen - Rakowski, Jana; Reis, Oliver (Projektbericht 1: Modelle, Transformationen, Corona-Erfahrungen)

Zur Differenz zwischen Modell und Gemeindeentwicklung in der Praxis - Reis, Oliver (Projektbericht 1: Modelle, Transformationen, Corona-Erfahrungen)

Modellprojekt Entwicklung der ehrenamtlichen Mitverantwortung, Projektbericht 1: Modelle, Transformationen, Corona-Erfahrungen

„Wer alles hinterfragen will, muss mit dem Boden der Tatsachen anfangen“. Narrative und ihre Funktionen, Chancen und Grenzen in der religionspädagogischen Forschung - Reis, Oliver (Theo-Web)